Family Environment And English Ability Among Islamic Elementary Students: Lingkungan Keluarga Dan Kemampuan Bahasa Inggris Siswa Sekolah Dasar Islam Terpadu - Rahmah At Tafani; Muhamad Sofian Hadi; Ahmad Fadly (Academia Open, 2026)
General Background: English language competence at the elementary level is widely recognized as a foundational academic skill within globalized education systems. Specific Background: In Indonesian Islamic integrated primary schools, family environment is frequently positioned as a key contextual factor accompanying formal English instruction. Knowledge Gap: Despite extensive theoretical assumptions, empirical evidence remains limited regarding whether variations in family environment categories are statistically associated with English language ability among SDIT students. Aims: This study examined the association between family environment categories and English language ability levels among students at SDIT Al Ihsan South Jakarta. Results: Quantitative analysis using a chi-square test revealed that most students were classified within a moderate family environment category, while English language ability predominantly fell within the high category; however, no statistically significant association was identified between the two variables (p = 0.550). Novelty: The study provides context-specific empirical evidence demonstrating the absence of a statistically meaningful association between categorized family environment and English language ability within an Islamic integrated primary school setting. Implications: These findings suggest that English language achievement at the elementary level should be understood through a broader educational ecosystem, where school-based instructional quality and learner motivation warrant greater analytical attention alongside family-related factors. Highlights • English ability levels remained high across differing family environment categories• Family environment classification showed no statistical association with language outcomes• School-based learning context emerged as a key explanatory consideration Keywords Family Environment; English Language Ability; Islamic Elementary School; Parental Involvement; Primary Education